Public sector reform, intergovernmental relations and the future of Australian federalism - Painter, Martin (1998)
Recent developments in the reform of intergovernmental relations have been influenced by contemporary models of public sector reform. Their systematic application to intergovernmental administration, in particular the manner in which jointly funded and managed programs are organised, may have profound and unanticipated effects on the federal system. When viewed in the context of a recent history of collaborative policy-making between political executives, the possibility that new forms of intergovernmental joint policy-making and program management might become the norm poses serious challenges to federal traditions of dual government. Arm's length and collaborative forms of joint decision making are contrasted as ideal types, and then used to analyse two case studies in collaborative intergovernmental decision-making - National Competition Policy and the National Training Agreement. It is concluded that the system-wide implications are profound if they are part of a broader trend, but caution is expressed about the powers of inertia and resistance in traditional forms of federal politics. - Reproduced
Keywords: Federalism - Australia; Public administration - Australia; Administrative reform